(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
The library is an environment where many people think of it as simply a place to borrow books. The library can carry out various activities, such as organizing and hosting cultural events or exhibitions. This article aims to analyze how the library, as a public space, can promote cultural activities for society. The methodology used was exploratory in nature, using bibliographic and qualitative research. Cultural activities aim to bring together the community that lives near the library, so that, through exhibitions and cultural activities, it can promote culture and make it accessible to the public. The conclusion is that the library has the potential to promote cultural activities and events that foster greater engagement between the library and the community.